Evaluating the Reliability and Consistency of Treadmill Gait Analysis Using an RGB-D Camera: Effects of Assistance and No Assistance - Yuichiro Hosoi; Takahiko Sato; Akinori Nagano (Sensors)
This study aimed to assess the intraday reliability of markerless gait analysis using an RGB-D camera versus a traditional three-dimensional motion analysis (3DMA) system with and without a simulated walking assistant. Gait assessments were conducted on 20 healthy adults walking on a treadmill with a focus on spatiotemporal parameters gathered using the RGB-D camera and 3DMA system. The intraday reliability of the RGB-D camera was evaluated using intraclass correlation coefficients (ICC 1, 1), while its consistency with the 3DMA system was determined using ICC (2, 1). The results demonstrated that the RGB-D camera provided high intraday reliability and showed strong consistency with 3DMA measurements regardless of the presence of an assistant. The Bland–Atman analysis indicated no significant systematic bias, with the minimum detectable change remaining within acceptable clinical ranges. These findings highlight the potential of the RGB-D camera for reliable markerless gait analysis in clinical environments in which walking assistance may be needed, thereby expanding its applicability in patients with various impairment degrees. Future research should validate these results in patient populations and explore their utility for measuring kinematic parameters.